2008
DOI: 10.2337/dc07-1794
|View full text |Cite
|
Sign up to set email alerts
|

Does Anodyne Light Therapy Improve Peripheral Neuropathy in Diabetes?

Abstract: OBJECTIVE -The purpose of this study was to determine the efficacy of anodyne monochromatic infrared photo energy (MIRE) in-home treatments over a 90-day period to improve peripheral sensation and self-reported quality of life in individuals with diabetes.RESEARCH DESIGN AND METHODS -This was a double-blind, randomized, sham-controlled clinical trail. We randomly assigned 69 individuals with diabetes and a vibration perception threshold (VPT) between 20 and 45 V to two treatment groups: active or sham treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 21 publications
0
58
0
Order By: Relevance
“…Three retrospective observational studies [14][15][16] showed MIPE to be effective based on chart review. Interestingly, a randomized controlled trial of photo energy used at home failed to show the modality to be therapeutically effective [17]. In that particular study, moreover, patients were trained to use a MIPE machine at home and were evaluated before and after 90 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Three retrospective observational studies [14][15][16] showed MIPE to be effective based on chart review. Interestingly, a randomized controlled trial of photo energy used at home failed to show the modality to be therapeutically effective [17]. In that particular study, moreover, patients were trained to use a MIPE machine at home and were evaluated before and after 90 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to previous research, although the present study provided greater photo energy per treatment, the total duration of treatment was shorter in our study (2 weeks versus 4 weeks to 3 months). 7,18 In addition, our study provided fewer treatment sessions than those of other studies (6 sessions versus 12-90 sessions). 7,18 The effects of phototherapy are time dependent.…”
mentioning
confidence: 50%
“…7,18 In addition, our study provided fewer treatment sessions than those of other studies (6 sessions versus 12-90 sessions). 7,18 The effects of phototherapy are time dependent. 6 The MIRE therapy initiates the release of NO, with subsequent biochemical and physiological changes.…”
mentioning
confidence: 50%
See 2 more Smart Citations